2014
DOI: 10.1111/cei.12265
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of an miR155 inhibitor by anti-CD20 single-chain antibody into B cells reduces the acetylcholine receptor-specific autoantibodies and ameliorates experimental autoimmune myasthenia gravis

Abstract: SummaryMicroRNA-155 (miR155) is required for antibody production after vaccination with attenuated Salmonella. miR155-deficient B cells generated reduced germinal centre responses and failed to produce high-affinity immunoglobulin (Ig)G1 antibodies. In this study, we observed up-regulation of miR155 in the peripheral blood mononuclear cells (PBMCs) of patients with myasthenia gravis (MG), and miR155 was also up-regulated in torpedo acetylcholine receptor (T-AChR)-stimulated B cells. We used an inhibitor of miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 72 publications
1
20
0
1
Order By: Relevance
“…However, there is increasing evidence to suggest that MG arises from the interaction of multiple genes. For instance, several members of the nuclear factor- (NF-) κ B signaling pathway work cooperatively to trigger an immune response in MG [ 13 ], and a recent study found that miR-155 was upregulated in MG patients, while suppressing miR-155 impaired NF- κ B signaling [ 14 ]. Since functionally connected pathways crosstalk through common sets of genes [ 15 ], identifying miRNAs and their target genes that are dysregulated in MG is critical for developing effective treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is increasing evidence to suggest that MG arises from the interaction of multiple genes. For instance, several members of the nuclear factor- (NF-) κ B signaling pathway work cooperatively to trigger an immune response in MG [ 13 ], and a recent study found that miR-155 was upregulated in MG patients, while suppressing miR-155 impaired NF- κ B signaling [ 14 ]. Since functionally connected pathways crosstalk through common sets of genes [ 15 ], identifying miRNAs and their target genes that are dysregulated in MG is critical for developing effective treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are also responsible for NS functionality, being implicated in translation, RNA metabolism, gene development and regulation [252]. Many NSDs such as Alzheimer's disease (AD), epilepsy, Parkinson's disease (PD), glioblastoma (GBM), multiple sclerosis (MS), and myasthenia gravis (MG) are caused in part by aberrant expressions and/or dysfunctions of miRNAs [251,[253][254][255][256][257].…”
Section: Mirnas In Nervous System Disordersmentioning
confidence: 99%
“…Also, miRNAs play important roles in the most lethal brain tumor (GBM) in cellular proliferation, apoptosis, invasion, angiogenesis and stemness [255]. In MS and MG, evidence indicates the implication of miR-132, miR-124, and miR-155 [257,260]. A brief summary of miRNAs implicated in neurologic disorders is provided in Table 4.…”
Section: Mirnas In Nervous System Disordersmentioning
confidence: 99%
“…They have demonstrated that AID is required for immunoglobulin gene diversifi cation in B lymphocytes, and it also promotes chromosomal translocations, suggesting that miR-155 can act as a tumor suppressor by reducing potentially oncogenic translocations generated by AID [ 58 ]. Wang et al have recently demonstrated that knockdown of miR-155 disrupts the B-cell-activating factor (BAFF)-R-related signaling pathway and reduces the translocation of nuclear factor (NF)-κB into the nucleus [ 59 ].…”
Section: Mir-155mentioning
confidence: 99%